FLOURISHING MAHASISWA: PERSPEKTIF TEORI KONSTRUKTIVISME JEAN PEAGET: FLOURISHING STUDENTS: A PERSPECTIVE OF JEAN PEAGET'S THEORY OF CONSTRUCTIVISM - I DEWA AYU EKA PURBA DHARMA TARI (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Students who are in the formal operational stage, where they have the ability to think abstractly and critically, have the potential to achieve flourishing. Students experience increased responsibility and competition in various aspects of their lives, such as academics, work, family, social, and personal interests. By understanding the relationship between flourishing and Piaget's cognitive development theory, we can create better support programmes for university students. This research uses a literature study method through the review of theoretical literature, references, and other scientific literature. Using Piaget's theory of constructivism, students can achieve flourishing through active learning, deep engagement, autonomy development, and relevant and contextualised learning experiences. An educational environment that provides freedom and flexibility allows students to develop optimal formal operations thinking ability, which is an important basis for achieving flourishing in higher education.